Fluorescence imaging after intraoperative intravenous injection of indocyanine green for detection of lymph node metastases in colorectal cancer. Issue 9 (September 2015) - Liberale, G.; Vankerckhove, S.; Galdon, M.G.; Donckier, V.; Larsimont, D.; Bourgeois, P.
Abstract Purpose This short communication aims at reporting the potential role of ICG fluorescence imaging after an intraoperative IV injection in the detection of lymph nodes (LNs) of a colorectal cancer origin. Patients and methods Two patients who were included in a protocol study evaluating the role of ICG in the detection of peritoneal metastases of colorectal origin (Protocol NCT-01995591) also had fluorescent LNs at exploration with a dedicated near-infrared camera system (Photodynamic Eye, PDE; Hamamatsu Photonics, Hamamatsu, Japan). An IV injection of ICG was delivered intraoperatively at 0.25 mg/kg. All LNs were also explored for their fluorescence, and tumor to background ratio (TBR) was calculated with IC-Calc 2.0 program. Results One patient had two retroperitoneal lymph node metastases and one mesocolic on a pre-operative work-up. The three tumoural lymph nodes at histopathology were hyperfluorescent in comparison to other uninvolved LNs. One patient had no pre-operatively known LN metastases and had one epigastric hyperfluorescent LN discovered at intraoperative exploration. This LN of 6 mm in size was malignant at histopathology. Conclusion This is the first report about tumoural LN of colorectal cancer origin detected by fluorescence imaging with intraoperative IV free-ICG injection. ICG fluorescence imaging by intraoperative IV injection represents an easy method for detecting metastatic LNs in colorectal cancer. This proof of concept should lead to further research in this field.